2020
DOI: 10.3389/fimmu.2020.00569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hyaluronan Treatment in Intestinal Innate Host Defense

Abstract: Hyaluronan (HA) is best known as an abundantly present extracellular matrix component found throughout the body of all vertebrates, including humans. Recent evidence, however, has demonstrated benefits of providing HA exogenously as a therapeutic modality for several medical conditions. Here we discuss the effects of providing HA treatment to increase innate host defense of the intestine, elucidate the size specific effects of HA, and discuss the role of various HA receptors as potential mediators of the HA ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…Our recent data indicate HA 35 KDa is also protective in a murine model of NEC, reducing incidence, severity, and mortality in the intraperitoneal dithizone/oral Klebsiella pneumoniae NEC model [25,46]. In addition, growing evidence supports the ability of endogenous HA to enhance the normal development of the gut [38,57]. Neonatal mouse pups treated from P7-14 with PEP-1, a HA binding inhibitor, exhibit a 30% reduction in intestinal epithelial stem cell proliferation and pronounced intestinal atrophy [38].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our recent data indicate HA 35 KDa is also protective in a murine model of NEC, reducing incidence, severity, and mortality in the intraperitoneal dithizone/oral Klebsiella pneumoniae NEC model [25,46]. In addition, growing evidence supports the ability of endogenous HA to enhance the normal development of the gut [38,57]. Neonatal mouse pups treated from P7-14 with PEP-1, a HA binding inhibitor, exhibit a 30% reduction in intestinal epithelial stem cell proliferation and pronounced intestinal atrophy [38].…”
Section: Discussionmentioning
confidence: 85%
“…Hill et al demonstrated that oral HA, purified from HM, increased the expression of human β-defensin 2 (hBD-2) and protected against Salmonella infection in vivo and in vitro [21,56]. HA 35 KDa appears to mimic the effects of bulk HM HA, increasing expression of mBD-3, the murine equivalent of hBD-2, and modulates epithelial zonula occludens-1 (ZO-1) expression, preventing bacterial translocation in multiple models of colitis [20,57]. Our recent data indicate HA 35 KDa is also protective in a murine model of NEC, reducing incidence, severity, and mortality in the intraperitoneal dithizone/oral Klebsiella pneumoniae NEC model [25,46].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with more than 95% of unfragmented radiolabeled high-molecular-weight HA excreted in the faeces after oral administration to rats and dogs ( Balogh et al ., 2008 ), which confirms no degradation. As the uptake of HA into epithelial cells is dependent on its molecular size it can be concluded that HA derived effects emerge from the lumen of the colon ( Kim and de la Motte, 2020 ). However, an in-depth study on the impact of molecular weight of HA in such drug combination would require additional investigation to determine to which extent the biodegradation of HA after rectal administration leads to resorbable components and subsequent changes in therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The biologic effects of HA are mediated primarily through receptor binding ( 25 ). HA binds to CD44, TLR2, TLR4, the receptor for HA-mediated motility (RHAMM), layilin, lymphatic vessel endothelial HA receptor- 1(LYVE-1), and HA receptor for endocytosis ( 26 ). Here we will focus on CD44, TLR2 and TLR4.…”
Section: Ha: Fragment Size Receptors and Biologic Effectsmentioning
confidence: 99%